Game-Based Basic Running Movement Model for Children U-10 at the BTB-Delapan Futsal Club - Moch Yanuar Iqbal; Taufik Rihatno; Eko Prabowo (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2023)
Objective. The aim of this study is to develop a basic framework for a running program suitable for children under the age of ten, who are members of the BTB-Delapan futsal club. The program is designed to align with the growth and development aspects, as well as the specific characteristics, of this age group. It is presented as a physical activity game that emphasizes fundamental running movements. Material and Method. The BTB-Delapan futsal club has successfully implemented a rudimentary running technique for children under 10 years old. This was achieved through R&D research that utilized the ADDIE approach, which involves the following steps: analysis, design, development, implementation, and evaluation. Result. This research has produced 13 game-based models that focus on the basic running movements of children under the age of 10. These models have been specifically designed to align with the growth and movement development characteristics of this age group, making them highly effective for use in training and improving the running techniques of children under 10. Conclusion. After undergoing a thorough review and enhancement process by qualified professionals, the fundamental game-oriented running motion model product has been deemed appropriate and fit for employment. Its technical specifications and performance metrics have been scrutinized to ensure its suitability for advanced users.